2008
DOI: 10.1159/000118030
|View full text |Cite
|
Sign up to set email alerts
|

Leukopoiesis Is Not Affected after Intravenous Treatment with the Novel Antineoplastic Agent Taurolidine

Abstract: Background/Aim: Chemotherapy can induce serious leukopenia. The aim of our study was to investigate the effects on leukopoiesis when the antineoplastic agent taurolidine (TRD) is administered by a bolus injection or during repetitive treatment (21 cycles) over 7 days in rats. Methods: Rats were intravenously treated with a single injection (A) or by a 7-day treatment (B) with increasing doses of TRD versus control (isotone sodium) in a standardized animal model. Hematological adverse effects on leukopoiesis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…However, previous experimental studies with tumor load showed no influence of TRD in hemopoiesis, renal and liver function which are commonly affected by usual chemotherapeutics [5,8,30] .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, previous experimental studies with tumor load showed no influence of TRD in hemopoiesis, renal and liver function which are commonly affected by usual chemotherapeutics [5,8,30] .…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, after intraoperative use the overall side effects were not relevant in animal experiments [20] , and hemopoiesis was not inhibited [8] . This might be explained by a selective molecular mechanism [7] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, we decided to use the concentration as described in human standard therapy and suitable for intravenous (i.v.) injections and other animal studies with comparable total doses (28,29). We decided to use the commercially available ready-to-use TRD 2% solution, which has been already used in human i.v.…”
Section: Discussionmentioning
confidence: 99%
“…A bone marrow aspirate determined that the lower neutrophil count was not due to bone marrow suppression. In a study in rats, the administration of taurolidine did not affect leucopoiesis [29]. The dog was monitored daily for over 3.5 years after the administration of taurolidine and remained healthy.…”
Section: Discussionmentioning
confidence: 99%